Synthesis and crystal structures of N, N-diarylacetamides bearing two azulene rings. (7th December 2021) - Ito, Ai; Watanabe, Mayuko; Ishii, Ayako; Yamasaki, Ryu; Okamoto, Iwao
Graphical abstract: Highlights: The crystal structures of N, N -diarylamides bearing two azulenes were analyzed. The linkage position on azulene influences the dihedral angle to the amide plane. The N -(2-azulenyl) group is almost coplanar with the amide plane. Abstract: N, N -Diarylacetamides bearing two azulene rings on the amide nitrogen were synthesized and their crystal structures were determined. The dihedral angle between the amide plane and the aryl ring located on the same side as the amide oxygen atom is influenced by the position of linkage of the aromatic ring to the nitrogen atom, and a 2-azulenyl group located on the same side as amide oxygen atom tends to be coplanar with the amide plane. This feature may be useful in the design of molecular devices and supramolecules.